Molecular characterization of four ADAMTS13 mutations responsible for congenital thrombotic thrombocytopenic purpura (Upshaw-Schulman syndrome) - Hommais, Antoine; Rayes, Julie; Houllier, Anne; Obert, Bernadette; Legendre, Paulette; Veyradier, Agnes; Girma, Jean-Pierre; Ribba, Anne-Sophie (Thrombosis and Haemostasis, 2007)
ADAMTS13 mutations S203P, R268P, R507Q and A596V were previously identified in French patients with hereditary thrombotic thrombocytopenic purpura (TTP) (Upshaw-Schulman syndrome). Mutated recombinant (r) ADAMTS13 were transiently expressed in COS-7 cells and characterized in comparison with wild-type (WT) rADAMTS13.ADAMTS13 antigen was qualitatively and quantitatively estimated by electrophoretic analysis and ELISA. Enzymatic activity was qualitatively and quantitatively estimated using GST-VWF73,FRETS-VWF73 fragments and full-length rVWF-WT as substrates. The four mutants and rADAMTS13-WT were present within the cells. Secretion level of rADAMTS13-WT reached 1,200 ng/ml. The four mutations strongly altered the secretion and biological activity of rADAMTS13. The percentage secretion was 21, 38 and 17% for rADAMTS13-S203P, -R268P and -A596V compared with rADAMTS13- WT. rADAMTS13-R507Q concentration was under the detection limit of the assay. In the four cases, no enzymatic activity was detected. After concentration, we confirmed that mutations S203P and R268P totally abolished the proteolytic activity of ADAMTS13. Due to the very low protease concentration, activity of rADAMTS13-R507Q was below the threshold of the assays. rADAMTS13-A596V had no proteolytic activity towards the full-length rVWF-WT whereas it exhibited a decreased specific activity of about 30% of that of rADAMTS13- WT towards FRETS-VWF73 fragment. Binding study of mutated rADAMTS13-S203P, -R268P and -A596V showed that the three mutations strongly decreased the interaction of ADAMTS13 with VWF. In conclusion, the four mutations, which led to a secretion defect, a loss of enzymatic activity and a decreased binding to the substrate, are responsible for the hereditary TTP in patients.
Keywords: ADAMTS13; mutations; recombinant proteins; thrombotic thrombocytopenic purpura (TTP)